2019
DOI: 10.1016/j.jml.2019.104047
|View full text |Cite
|
Sign up to set email alerts
|

How many words do we read per minute? A review and meta-analysis of reading rate

Abstract: had a reading rate of 3.9 words per second (234 wpm), the latter a rate of 7.3 words per second (438 wpm). Unfortunately, no information was given about how reading rate had been established. This encouraged Huey (1901) to reassess the issue. He selected 11 pages from an interesting novel, each containing 405 words, which presented no peculiar difficulties to the reader. Twenty university students were asked to read one page at a time while Huey measured the time with a stopwatch. There were 10 conditions. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
136
0
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 257 publications
(199 citation statements)
references
References 350 publications
11
136
0
12
Order By: Relevance
“…For instance, in meaningful text reading, semantic and conceptual top-down information contribute to the process of word recognition. In addition, Brysbaert (2019) reported an average reading aloud rate in typical readers of 183 words per minute, which is close to the reading rate reported for the Alouette Test (Cavalli et al 2018; see Table 6), but one standard deviation above the reading rate we observed with the Flamingo test (Table 6). A possible factor may be the length or imageability of the words in the text.…”
Section: Discussionsupporting
confidence: 81%
“…For instance, in meaningful text reading, semantic and conceptual top-down information contribute to the process of word recognition. In addition, Brysbaert (2019) reported an average reading aloud rate in typical readers of 183 words per minute, which is close to the reading rate reported for the Alouette Test (Cavalli et al 2018; see Table 6), but one standard deviation above the reading rate we observed with the Flamingo test (Table 6). A possible factor may be the length or imageability of the words in the text.…”
Section: Discussionsupporting
confidence: 81%
“…A number of key findings emerged in the global analyses of literacy differences in eye-movement control. Overall lower literate readers showed longer average first-pass reading times (first-fixation duration and gaze duration) as well as longer total reading times and slower reading rates, replicating prior work (Ashby et al, 2005; Brysbaert, 2019; Chace et al, 2005; Kuperman & Van Dyke, 2011). Beyond effects on average fixation durations, we focused specifically on the underlying fixation duration distributions to quantify individual differences in intra-individual variability in eye-movement control during reading.…”
Section: Discussionsupporting
confidence: 79%
“…We report two average measures of first-pass word fixation durations: first-fixation durations (duration of the first fixation on each word) and gaze durations (i.e., first-pass reading times: the sum of all first-pass fixations on each word before moving off the word), as well as total reading time (sum of all fixations on each word). In addition, we report an estimate of reading rate in words per minute in order to facilitate a descriptive comparison in gross reading speed between this sample and prior work (e.g., Brysbaert, 2019). Three saccade-based measures are also presented: the probability of regressing (i.e., that the eyes move left to an earlier word from the target), the probability of skipping (the proportion of words skipped during first-pass reading), and the probability of refixation (i.e., that a word was fixated more than once during first-pass reading).…”
Section: Methodsmentioning
confidence: 99%
“…Given the particular importance of good reading skills in current academic and professional settings, the investigation of reading rate (i.e., number of words or letters read per time unit; Brysbaert, 2019; Meyer et al., 1999) and reading comprehension (i.e., accessing and constructing meaning from written text; Johnston et al., 2008) represents a research field of high social and economic significance. In particular, the relationship between reading rate and the complex process of comprehension, which requires the coordination of multiple levels of language and cognitive functions (Landi & Ryherd, 2017), has been in the centre of interest for empirical and theoretical research questions.…”
mentioning
confidence: 99%